2018
DOI: 10.1002/chem.201802175
|View full text |Cite
|
Sign up to set email alerts
|

Intercepting a Transient Phosphino‐Arsinidene

Abstract: A phosphino-arsinidene derived from a diazaphospholidine scaffold (Ar**NCH ) PAs (where Ar**=2,6-bis[(4-tert-butylphenyl)methyl]-4-methylphenyl) was generated in situ and trapped with a range of reagents. Metathesis reactions between (Ar**NCH ) PCl and either [Na(18-crown-6)][AsCO] or [Na(dioxane) ][AsCO] are believed to afford an arsaketene, (Ar**NCH ) PAsCO, which readily loses carbon monoxide under ambient conditions. The resulting transient arsinidene was shown to undergo cycloaddition reactions with exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The As−P bond length is 2.2152(6) Å, which is almost identical with the As−P distances reported for the cationic C 2 ‐symmetric compound [(IDipp)PAsP(IDipp)]Cl (2.203(1) Å) and for the bimetallic AsP complex F (2.2324(13) Å) . Slightly longer bonds were found for other related NHC arsenic–phosphorus systems, for example 2.3133(4) Å in [(SIMes)PAs( t Bu) 2 ] or 2.3552(6) Å in the IDipp adduct of a transient phosphino–arsinidene (SIMes=1,3‐bis(2,4,6‐trimethylphenyl)imidazolidin‐2‐ylidene) …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The As−P bond length is 2.2152(6) Å, which is almost identical with the As−P distances reported for the cationic C 2 ‐symmetric compound [(IDipp)PAsP(IDipp)]Cl (2.203(1) Å) and for the bimetallic AsP complex F (2.2324(13) Å) . Slightly longer bonds were found for other related NHC arsenic–phosphorus systems, for example 2.3133(4) Å in [(SIMes)PAs( t Bu) 2 ] or 2.3552(6) Å in the IDipp adduct of a transient phosphino–arsinidene (SIMes=1,3‐bis(2,4,6‐trimethylphenyl)imidazolidin‐2‐ylidene) …”
Section: Figurementioning
confidence: 99%
“…[17] Slightly longer bonds were found for other relatedN HC arsenic-phosphorus systems, for example 2.3133(4) in [(SIMes)PAs(tBu) 2 ] [23] or 2.3552(6) in the IDipp adduct of at ransient phosphino-arsinidene (SIMes = 1,3bis(2,4,6-trimethylphenyl)imidazolidin-2-ylidene). [24] Reduction of 3 with two equivalents of potassium graphite (KC 8 )i nT HF afforded [(IMes)AsP(IDipp)] (4)w hich was isolated as ad ark red solid in 37 %y ield (Scheme 1). The 31 PNMR spectrum (in C 6 D 6 ,F igure S8, Supporting Information) showeda broad signal at À60.6 ppm, whichl ies between the chemical shifts established for the homoleptic diphosphoruss pecies [(IDipp)P 2 (IDipp)] (B, À52.4 ppm) and [(IMes)P 2 (IMes)] (À73.6 ppm), [6] whereas the heteroleptic congener [(IMes)-P 2 (IDipp)] afforded two doubletsw ith similar chemical shifts at À63.1 and À59.4 ppm ( 1 J PP = 249 Hz).…”
mentioning
confidence: 99%
“…Unlike nitrenes and phosphinidenes, the triplet species of heavier group 15 elements are highly unstable and have only been investigated in the gas phase and in low‐temperature matrices. However, Bertrand et al recently reported on a stable singlet (phosphanyl)phosphinidene, and the corresponding (phosphanyl)arsinidene was observed as a transient species in solution . In addition, these reactive species were electronically stabilized by coordination to Lewis acidic metal centers as well as base‐coordination .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Goicoechea and Hinz developed a method of generating the 2‐arsaethynolate anion, which was prepared from nonvolatile elemental arsenic . This method has been applied to obtain various unique arsenic‐containing molecules and complexes …”
Section: Introductionmentioning
confidence: 99%
“…[35] This method has been appliedt oo btain variousu nique arsenic-containing molecules and complexes. [35][36][37][38][39] In this context,n onvolatile intermediate transformation (NIT) methodsa re effective for promoting the advancement of organoarsenic chemistry.C yclooligoarsines are key synthetic intermediates for the developmento fp ractical AsÀCb ond formation reactions. It is worth noting that they can be safely prepared from nonvolatile inorganic arsenic compounds, and that the resulting materials have relatively high molecular weight and show negligible volatility under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%